Essential Trace and Toxic Element Content in Lacaune Sheep Milk during Lactation - Zvonko Antunović; Boro Mioč; Josip Novoselec; Ivan Širić; Valentino Držaić; Željka Klir Šalavardić (Foods, 2023)
The aim of this study was to investigate the concentrations of essential trace and toxic elements in the milk of Lacaune sheep during lactation in intensive rearing systems. This research was conducted with 30 Lacaune sheep that were monitored in the early (60 days of lactation), medium (120 days of lactation), and late (180 days of lactation) stages of lactation. The sheep were fed a pelleted feed mixture (1 kg/day), a cereal mixture (600 g/day), and alfalfa hay (ad libitum). The essential (Fe, Zn, Cu, Co, Mn, Mo, Se, Cr, and Ni) and toxic element (heavy metals: Cd, Pb, As, and Hg) concentrations in the feed and milk were determined using an inductively coupled plasma mass spectrometer. Significant variations in the main essential trace and toxic elements, except for the Mo, Se, Ni, As, and Hg concentrations, were found in the milk of Lacaune sheep during lactation. As lactation progressed, in the late stage of lactation, significantly higher concentrations of Co, Mn, Mo, Cr, and Pb were found, while Zn and Cu in the milk of Lacaune sheep decreased significantly (4.15 and 0.21 mg/kg) compared to their concentrations in the early stage of lactation (5.66 and 0.43 mg/kg). Significantly lower concentrations of Fe and higher concentrations of Cd were found in the medium stage (0.23 mg/kg and 1.08 µg/kg) of lactation compared to both the early and late stages of lactation. An analysis of the correlation coefficients between the essential trace and toxic elements in Lacaune sheep milk during lactation determined a significantly positive correlation between Fe:Cr, Fe:Mn, Fe:Co, Fe:Se, Zn:Ni, Zn:Se, Cr:Mn, Cr:Co, Cr:Se, Cr:Mo, Mn:Co, Mn:Pb, Co:Ni, Co:Se, Ni:Se, Se:Mo, Se:Pb, and Cd:Pb. A significantly negative correlation was also found between Cu:Mn, Zn:Mo, Cg:Hg, and Hg:Pb. Based on the obtained results, it is recommended that the influence of the stage of lactation, as well as the breed of sheep, should be included when designing experiments. In general, sheep milk is rich in essential trace elements, but it also contains a very low content of toxic elements, which provides justification for increasing the breeding of Lacaune sheep and indicates the convenience of consuming their milk without risking the consumer’s health.